Persepsi Guru Terhadap Pelaksanaan Ujian Nasional Peserta Didik Kelas IX Di Madrasah Tsanawiyah Negeri 1 Pangkalpinang - Handayani, Shelly Astuti; Janawi, Janawi (LENTERNAL: Learning and Teaching Journal, 2023)
The focus of this research is on the teacher's perception of the abolition of the National Examination of Class IX pupils. The aim of this study is to describe the perceptions of teachers of the removal of the national exam of students of class IX in Madrasah Tsanawiyah Negeri 1, Pangkalpinang, and the impact of the deletion of the national exam on class IX pupils in Madrasah Tsanawiyah Negeri 1. This research uses qualitative research methods, a type of descriptive research. Data collection techniques in this research include interviews and documentation. The information obtained by the researchers came from the teachers of the subject of the national examination and the teacher of Islamic religious education related to the removal of the national examinations. The data analysis techniques used in this study are data reduction, data presentation, and conclusion drawings. The results of the research showed that the perception of the teacher against the abolition of the National Examination raised several points of view, namely, Pro against the elimination of the national examination because of the assumption that with the removal of national examinations students could develop and express their skills based on individual talents and abilities because the successes and failures of the students are not sufficiently measured and determined by the scores of the subjects of the country examination and the disadvantages due to the deletion of the nation examination students become individuals who are prone to indifference to lessons such as the soul is irresponsible and the loss of motivation in learning and the positive impact of the cancellation of National Exams i.e. independence in learning while the negative impact of abolishing the National Test is related to the psychological kind of the emergence of the unresponsive soul and the enthusiasm of the student student.